1990
DOI: 10.1115/1.2920269
|View full text |Cite
|
Sign up to set email alerts
|

Micro-EHL in Lubricated Concentrated Contacts

Abstract: In sliding friction experiments, performed with lubricated concentrated contacts macroscopically operating in the lubricants’ liquid-state regime, the existence of micro-EHL has been shown. With the measuring method used, the lubricants’ limiting shear stress τ1 or the ratio of the limiting shear stress with pressure, τ1/p, can easily be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…By including the increasing conformity of the two bodies the load carrying capacity of the system is increased due to running in under mild conditions as the temperature field is lowered. This effect is also observed in the study done by Schipper et al [17]. This effect will be discussed more intensively in the results section of this article.…”
Section: Theorysupporting
confidence: 78%
“…By including the increasing conformity of the two bodies the load carrying capacity of the system is increased due to running in under mild conditions as the temperature field is lowered. This effect is also observed in the study done by Schipper et al [17]. This effect will be discussed more intensively in the results section of this article.…”
Section: Theorysupporting
confidence: 78%
“…7. The fluid film shear stress ô is expressed in terms of Newtonian and non-Newtonian behaviour and recognizes the existence of a limiting shear stress [30]. ó is the normal or Hertzian stress acting on the contact; hence, ô f = ó represents the traction coefficient.…”
Section: Contact Surface Shear Stressmentioning
confidence: 99%
“…Schipper et al. 19 suggested that micro-EHL is possible with the boundary lubrication condition below a certain value of surface roughness. The occurrence of micro-EHL indicates the presence of a thin lubrication film between the interacting asperities.…”
Section: Resultsmentioning
confidence: 99%